An investigation into the partition functions of the broad-host-range Plasmid pTF-FC2 - Smith, Anthony S G (Department of Molecular and Cell Biology, 2016)
The broad-host-range Thiobacillus ferrooxidans plasmid pTF-FC2 is stably inherited over many generations despite a low copy number. The pas genes which lie between the repB primase and the repA helicase encode a proteic plasmid stabilisation system and are capable of stabilising the unstable heterologous R1 replicon present on p0U82. The deletion of the pas genes has been shown not to change the copy number of mutant plasmids. This suggested that the pas genes are not involved in replication and function as a stabilisation cassette. The pasA gene encodes an antidote, the pasB gene a toxin which exerts a bacteriocidal effect in an E. coli host and the pasC gene a protein which moderates the toxic effect of PasB. The PasC is unique in proteic plasmid stabilisation systems and reduces PasB toxicity only in the presence of PasA. PasA is able to repress the pas promoter and the addition of PasB increases this repression. PasC has been shown not to effect the pas promoter by itself. In the presence of PasA and PasB, PasC reduces the ability of PasA and PasB to repress the pas promoter. PasC is thought to stabilise the interaction of PasA and PasB and in doing so reduces their ability to function as repressors of the pas operon. The IncQ plasmid RSF1010 which has similarity to pTF-FC2 has two genes in a position analogous to the pasA, pasB and pasC genes. These genes have been found to be unable to function as a plasmid stabilisation system.